A Source-Studies Approach to Michael Nyman’s Score for "The Draughtsman’s Contract" - Cooper, David; Sapiro, Ian (Journal of Film Music, 2011)
The composer Michael Nyman has donated a unique collection of his original sound materials and other documentation to the University of Leeds on long-term loan for scholarly investigation. There are more than 500 individual items in the archive, which includes film, television and concert music, as well as associated items of paperwork, and the films directed by Peter Greenaway feature strongly in the collection. Evidence for the underlying creative processes in film composition can be found within the source materials which include the source recordings and stereo mixdowns of cues, materials often disposed of by film and television companies after a film’s release or TV program’s broadcast. This article questions the extent to which the surviving audio and supporting documentary materials reflect the development of the score and the relationships between Nyman’s music and Greenaway’s images as exemplified in the non-mainstream film "The Draughtsman’s Contract".